COMPETITIVENESS OF THE ENTERPRISE IN THE CONDITIONS OF THE INFORMATION SOCIETY - PUKHALSKA, Yana (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article considers modern aspects of enterprise competitiveness in the information society. Factors influencing the consumer of the information society era are described. The conceptual content of modern competitive advantages of the enterprise and the information system for creating new competitive advantages based on the monitoring results are determined. The possibility of ensuring the competitive advantages of the enterprise in the information society has been studied on the presence of which factors. The basis of the competitiveness of the enterprise requires thorough research on evolutionary development, current manifestations in the period of transformation of economic relations and increasing uncertainty, global challenges of the external environment. In the process of building an information society, taking into account its specifics, approaches to competition analysis are changing. Innovation processes have their own characteristics and the analysis of competitive advantages should be carried out taking into account the dynamic development of the economy. Significant changes in the functioning of socio-economic systems make it necessary to study the main factors of enterprise development in the new conditions, as well as the study of basic reserves for the formation of competitive advantages. For successful operations in such conditions, businesses are no longer efficient enough to manage their material resources. Intellectual resources and the result of their effective use - intellectual capital - are the basis for the formation of a sustainable level of competitiveness of enterprises. It is necessary to consider modern aspects of enterprise competitiveness in the information society; identify factors that affect the consumer of the information society; determine the conceptual content of modern competitive advantages of the enterprise.